Psychosocial predictors of attitude toward premarital sexual practice among university students, Ethiopia - Yedemie, Yordanos Yibeltal (Frontiers in Psychology, 2024)
Objectives: Premarital sexual practice during adolescence may lead to different sexual and reproductive health problems, including HIV/AIDS. The objective of this study was to assess psychosocial predictors of attitudes towards premarital sex among Bahir Dar University students.A correlational design was used. A multi-stage sampling technique was used to select 375 respondents for the study, although the analysis was based on the 361 questionnaires that were returned from the field and found useful for analysis. Data was collected using a selfdeveloped and modified instrument on standardized scales. The internal consistency of the Perception of Peer Pressure Scale was 0.83, while the self-esteem measuring scale had a reliability of 0.77. The internal consistency of the sexual attitude inventory scale was 0.97. The data were quantitatively analyzed using (inferential statistics) logistic regression, one sample t test, and an independent sample t test. Results: The findings of the study showed that all the psychological variables investigated were found to significantly predict premarital sexual relationships among the respondents. Male students with the experience of premarital sex have a higher level of self-esteem and exposure to peer pressure than their female counterparts. A study suggests that male students with the experience of premarital sex have a higher level of selfesteem and exposure to peer pressure than their female counterparts. Self-esteem negatively predicted attitudes towards premarital sex. Conclusion: Scaling up the level of school counseling, especially in the area of sexual adjustment and modification of the psychological variables investigated, was recommended.